A descriptive-contrastive analysis of the word order of some English and Ilonggo relater-axis phrases - Martinez, Fe Tavarro 1926- (s.n.], 1969)
The study presented selected types of English and Ilonggo relater-axis phrases, which are classified according to the kind of relationship indicated. Specifically, the study aims to provide a descriptive-contrastive analysis of the word order of some English and Ilonggo relater-axis, to predict the learning difficulties of Ilonggo learners of English, and to provide a guide for teachers for the construction of teaching materials in English for Ilonggo learners.